Alternative Hedonism and the Critique of Consumption in the Philosophical Thought of Kate Soper - Függ, Zsolt Péter (Acta Cultura et Paedagogicae, 2023)
The focus of this paper is on the philosopher Kate Soper, author of at least a dozen books on feminism and continental philosophy. She has been involved in numerous environmental and peace movements in the UK and elsewhere in Europe, and her work on ecological issues is partly influenced by this. She has published numerous articles in Radical Philosophy, New Left Review and Capitalism Nature Socialism. This paper attempts to summarise her theory of 'alternative hedonism'.